The link between productivity and wages: the role of the minimum wage in Portugal - Afonso, João Pedro De Oliveira (2023)
An increase in the Portuguese minimum wage has been positively correlated with the relationship between productivity and wages on the 90-10 and 50-10 percentile differences, respectively. Applying a fixed effects regression, this paper shows that the minimum wage, measured through the relative minimum wage, had two reverse but complementary effects: it has led to a compression of the wage distribution through its wage biting effects and, simultaneously, led to strengthening of the correlation between wages and productivity dispersions, between-firms within each sector. The results found are being driven by the service sector of the economy.